2019
DOI: 10.3102/0013189x18820291
|View full text |Cite
|
Sign up to set email alerts
|

School Teasing and Bullying After the Presidential Election

Abstract: In response to media reports of increased teasing and bullying in schools following the 2016 U.S. presidential election, we investigated its prevalence with a Virginia school climate survey completed by approximately 155,000 seventh- and eighth-grade students in 2013, 2015, and 2017. Survey results were mapped onto presidential election results for each school division’s locality. In localities favoring the Republican candidate, there were higher adjusted rates of students reporting that (a) they had experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 62 publications
2
57
0
Order By: Relevance
“…Similarly, political and/or election data pertaining to schools’ locations are not available from the SCS. Huang and Cornell () find evidence that localities’ political orientation was associated with increased bullying after the 2016 U.S. Presidential election. Future studies of both bullying and hate may consider the impact of local political leanings as well.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, political and/or election data pertaining to schools’ locations are not available from the SCS. Huang and Cornell () find evidence that localities’ political orientation was associated with increased bullying after the 2016 U.S. Presidential election. Future studies of both bullying and hate may consider the impact of local political leanings as well.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a 2018 Pew Research Center survey, about half the Latino/a respondents said that the situation for Latino/as in the United States had worsened over the past year, the majority worried that they or someone they know could be deported, and two thirds said that the Trump administration's policies were harmful to Latino/as (Lopez et al, 2018). These patterns were reflected in a study of bullying by Huang and Cornell (2019), which found that in school localities in Virginia, in which a majority of voters had supported Trump in the 2016 election, student rates of reporting bullying incidents were 18% and 9% higher for responses indicating that they had been teased "because of their race or ethnicity," respectively. The authors found no meaningful differences across schools for these two indicators before the 2016 presidential election.…”
Section: Background and Theoretical Frameworkmentioning
confidence: 97%
“…As studies of bullying steadily increase in Mexico (e.g., Baruch-Dominguez et al 2016;Ramos-Jiménez et al 2017;Romo and Kelvin 2016), this may result in additional policy and school-based prevention efforts to address bullying. On the other hand, that Latinx US youth actually reported higher rates of victimization exposure than Mexican youth highlights a need to ensure US-based prevention programming is adequately addressing the risk posed to Latinx youth; a risk that may be on the rise given growing racial tensions in the current US political climate (Huang and Cornell 2019).…”
Section: Discussionmentioning
confidence: 99%